Metal-catalyzed copolymerizations of epoxides and carbon disulfide for high-refractive index low absorbance adhesives and plastics - Schwarz, Derek B.; Patil, Anvay; Singla, Saranshu; Dhinojwala, Ali; Eagan, James M. (Frontiers in Chemistry, 2023)
High-refractive index plastics are useful materials due to their optical properties, ease of processing, and low-costs compared to their inorganic counterparts. Catalytic carbon disulfide (CS2) copolymerization with epoxides is one method for producing low-cost high refractive index polymers. The reaction is accompanied by an oxygen-sulfur exchange reaction which produces irregular microstructures in the repeating units. In this study, metal salen catalysts were investigated with different metal centers (Al, Cr, Co) and salen ligand electronics, sterics, backbones, and co-catalyst in the copolymerization of CS2 with propylene oxide (PO) and cyclohexene oxide (CHO). The results reveal the essential nature of Cr metal centers on reactivity and the backbone geometry on monomer selectivity. There were no significant impacts on the O-S exchange reaction when ligand design changed, however PO and CHO/CS2 copolymers yield different monothiocarbonate microstructures. Additionally, the effects of microstructure on optical and thermal properties were investigated using spectroscopic ellipsometry and calorimetry, respectively. The CHO system produced high Tg plastics (93 °C) with high refractive indexes (n up to 1.64), modest absorbance (κ < 0.020), and Abbe numbers of 32.2 while PO yielded low Tg adhesives (Tg = 9 °C) with high refractive indexes (n up to 1.73), low absorbance (κ < 0.005), and low Abbe numbers (VD = 19.1).